Making performance analysis of on grid photovoltaic energy systems: Example of Turkey - Kilic, Ugur; Kesen, Ugur (ACADEMIC PUBLICATION COUNCIL, 2022)
The globalizing world and the rapid increase in industrialization and urbanization rates have increased the world's need for energy day by day, making energy one of the most important agenda items of the world. Increasing demand has led the countries to ensure supply-demand balance to become one of the basic energy policies. One of these prominent energy policies is to ensure diversity in supply and to turn towards renewable resources that are not dependent on exhausted fossil fuels. One of these renewable sources is photovoltaic (solar cell) energy generation systems that generate electrical energy from solar energy. Solar energy is a good alternative to fossil fuels as it has an environmentally clean source feature. In this study, the performance evaluations of power plants were made by comparing the simulation results with data obtained from established fields in three different geographical regions of Turkey. In addition, regional production efficiency was analyzed by comparing the production values of the plants among themselves. An interface program that analyzes instant power plant values was designed, and a practical evaluation software was created.
Keywords: Sun grid solar energy; Photovoltaic energy; Renewable energy; Solar power; POWER-PLANT; PV; MODEL; Engineering